Non-destructive quality evaluation by sensing maturity and ripening of fruits and vegetables - Kumari, Pushpa; Ahmad , M Feza; Mir , H (Journal of Postharvest Technology, 2018)
Maturity at harvest is the most important factor determining its postharvest quality and storage potential of fresh fruits and vegetables.  Ripening is the process by which fruit attained desirable flavour, quality, colour and other textural properties. The characterization of fruit and  vegetables has been an important issue in the automatic sorting of fruits from the harvest site as well as from the cold storage.  Characterization technique for horticultural crops is divided into two groups, i.e. non-destructive and destructive technique. For commercial  scale packaging and other quality determination, non-destructive methods are useful as it govern essential quality parameters without any  physical damage of produce. It works on the principle of optical properties, sonic vibration, machine vision technique, nuclear magnetic  resonance (NMR), electronic noses, X-rays and computed tomography. Electronic nose technology sense aroma of fruit non-destructively,  which can be used to determine fruit ripening stages after harvesting. Some of these techniques are used at large scale, but some are used  only at laboratory level. These methods for evaluating maturity and ripening needs more initial investment.
Keywords: Non-destructive technique; ripening; maturity; fruits; vegetables